The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/ange.201711390
|View full text |Cite
|
Sign up to set email alerts
|

Synthese α‐chiraler Ketone und chiraler Alkane durch eine radikalisch/ionische Kreuzungsreaktion von Vinyl‐Bor‐At‐Komplexen

Abstract: Vinyl-Bor-At-Komplexe,h ergestellt aus Enantiomeren-angereicherten Alkylpinakolboronsäureestern, durchlaufen stereospezifische,r adikalisch induzierte 1,2-Wanderungen in radikalisch/ionischen Kreuzungsreaktionen. In dieser Dreikomponentenreaktion kçnnen verschiedene kommerziell erhältliche Alkyliodide als Radikalvorstufen verwendet werden, und Licht fungiert als Ketteninitiator.E ine nachfolgende Oxidation oder Protodeborylierung führt zu wertvollen a-chiralen Ketonen und chiralen Alkanen mit exzellenten Enant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Highly enantioenriched compounds are readily accessible by the radical polar crossover strategy using chiral alkyl boronic esters as substrates for the formation of the corresponding vinyl boron ate complexes. Along these lines, the radical‐induced 1,2‐boron ate rearrangement was successfully used for the preparation of α‐chiral ketones and enantioenriched alkanes, which were obtained after oxidation of the initial B‐containing products with sodium perborate and Dess–Martin periodinane or by protodeborylation, respectively (Scheme a) . In these processes, vinyl boron ate complexes derived from enantioenriched alkyl boronic esters and vinyllithium are reacted with various commercially available alkyl iodides.…”
Section: Radical‐induced 12‐boron Ate Shifts To Sp2 Carbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly enantioenriched compounds are readily accessible by the radical polar crossover strategy using chiral alkyl boronic esters as substrates for the formation of the corresponding vinyl boron ate complexes. Along these lines, the radical‐induced 1,2‐boron ate rearrangement was successfully used for the preparation of α‐chiral ketones and enantioenriched alkanes, which were obtained after oxidation of the initial B‐containing products with sodium perborate and Dess–Martin periodinane or by protodeborylation, respectively (Scheme a) . In these processes, vinyl boron ate complexes derived from enantioenriched alkyl boronic esters and vinyllithium are reacted with various commercially available alkyl iodides.…”
Section: Radical‐induced 12‐boron Ate Shifts To Sp2 Carbonsmentioning
confidence: 99%
“…Likely, polar effects play a key role in the selective α‐H‐abstraction of these anionic boron ate complexes by the electrophilic CF 3 radical (see below). Moreover, it is well established that CF 3 I is an excellent terminal oxidant for intermediates of type B , rendering this cheap iodide to be the reagent of choice to realize this interesting sequence . Ir(ppy) 3 was employed as a smart initiator upon irradiation with blue LEDs (Φ=8.8).…”
Section: Radical‐induced 12‐boron Ate Shifts To Sp3 Carbonsmentioning
confidence: 99%
“…[6] In particular, the rearrangement of vinylboronate complexes for the generation of alkylboronates has attracted considerable attention from many research groups ( Figure 1a). [8a] In 2017, three groups independently extended this elegant chemistry to the radical-polar crossover process using vinyl boronate complexes and alkyl halides triggered by Et 3 B/air, [9] visible light, [10] or nickel catalysts. [7] Half ac entury later, Morken et al reported an important breakthrough for 1,2-alkyl/aryl migration [8] through carbopallada-tion of vinylboronate complexes with different coupling partners.…”
mentioning
confidence: 99%
“…Starting with commercial N -Boc-pyrrolidine ( 4 ), enantiopure boronic ester 5 was prepared via a (+)-sparteine mediated asymmetric lithiation/borylation 5456. The ester moiety was introduced via stereospecific radical-induced 1,2-migration27,28 of the corresponding in situ generated vinyl and isopropenyl boron ate complexes with α-iodo acetates as radical precursors to provide 6 and 10 in 52% and 65% yield. In the coniceine route, 6 was directly subjected to the protodeboronation to provide the pyrrolidine 7 in 61% yield.…”
mentioning
confidence: 99%